Pengaruh profitabilitas, likuiditas, dan laverage terhadap nilai perusahaan (studi empiris pada perusahaan sub sektor perbankan yang terdaftar di Bursa Efek Indonesia (BEI) pada tahun 2020 - 2024) - Hendrika, Rosana Amelia; Nuryanto, Nuryanto (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2026)
This study aims to examine the influence of profitability (Return on Assets/ROA), liquidity (Current Ratio/CR), and leverage (Debt to Equity Ratio/DER) on firm value (Price to Book Value/PBV) in the banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Firm value reflects the market's perception of a company’s performance and future prospects, which is particularly crucial in the banking sector due to its strategic role in the national financial system. The research employs a quantitative approach using panel data regression, enabling both cross-sectional and time-series analysis. Data were obtained from audited annual financial reports published by the respective companies. The findings reveal that ROA has a positive and significant effect on PBV, CR shows no significant effect, and DER has a significant negative effect. Simultaneously, the three independent variables collectively influence firm value. These results contribute to the development of financial theories such as Signaling Theory and Pecking Order Theory and provide practical implications for formulating optimal financial strategies in Indonesia’s banking industry.